Accounting for Infrastructure Regulation : An Introduction - Rodriguez Pardina, Martin (Washington, DC: World Bank, 2012)
The Enron crisis offered a dramatic reminder to regulators around the world that reliable accounting standards are essential for markets to work efficiently and fairly. Harvey Pitt, chairman of the regulatory agency responsible for the monitoring of accountants in the United States (the Securities and Exchange Commission) from 2001 to 2003, argued that the crisis revealed two problems with accounting that needed to be addressed by the regulators. The first problem is that the accountants may have gotten some of the accounting wrong. The second, and more important, problem is that they may have gotten a lot of the accounting right. This volume describes a set of rules with which utilities monopolies should be able to comply without threat to a fair return on their business, while at the same time ensuring the accountability of all players. Regulators in many member countries of the organization for economic co-operation and development and in the electricity sector in many developing countries use these rules. There is no reason why they should not be of value to regulators of all public service providers that enjoy strong residual monopoly rights. Ultimately, this book is about rules for maintaining the minimum level of accountability needed to achieve fair treatment of investors, operators, users, and taxpayers alike and to prevent preferential treatment of the stakeholder with the highest political leverage at any point in time.